Pendidikan Pancasila dan Pendidikan Agama Islam Dalam Konteks Kehidupan Beragama - Firman Mansir; Lia Kian (Jayapangus Press, 2021)
This study explains the position of Pancasila Education and Islamic Religious Education in the context of religious life. There are several forms of the dynamics of religious life such as conflicts that usually occur in students, especially in various Indonesian educational institutions. Conflicts that often occur in schools are disputes between students, power struggles, small problems that are often brought up and teenage love problems. This phase students have begun to recognize feelings of love between the opposite sex. The results show that the position of Pancasila education and Islamic Religious Education is very strategic and occupies. The forefront because they are the mainstream in counteracting negative things for religious life. So, they play an active role in overcoming various violence and conflicts that occur in educational institutions. Thus, Pancasila education and Islamic Education make efforts to guide future generations of future candidates so that they can have a good personality and are certainly. In accordance with the norms of set by Islam itself through a strong religious understanding so that there are no conflicts between them.